Imino-stabilised phosphinidene (or azaphosphole?) and some of its derivatives12. Issue 47 (21st November 2018) - Nguyen, Minh Tho; Gabidullin, Bulat; Nikonov, Georgii I.
Abstract : Diiminophenyl (dimph) proved to be an excellent ligand platform to stabilise a low-valent phosphorus centre. Abstract : Diiminophenyl (dimph) proved to be an excellent ligand platform to stabilise a low-valent phosphorus centre. The resultant compound dimphP (3 ), which can be rationalized as an imino-stabilised phosphinidene or benzoazaphosphole, shows remarkable chemical stability: it withstands treatment with water and oxidizers (O2 and pyridine oxide) and only reacts with excess strong acid ( e.g. HCl) to generate the P(iii ) chloride (dimHph)PCl (7 ), where dimHph stands for a diiminophenyl group hydrogenated at one imine position. Surprisingly, substitution of the chloride under some nucleophilic (KOBu t ) and electrophilic conditions (Me3 SiOTf) regenerates the parent compound3, by proton removal from the weakly acidic CH2 N position. A related species (dimH2 ph)P (14 ), where dimH2 ph stands for diiminophenyl hydrogenated to imino(aminomethyl)phenyl, is produced upon thermal rearrangement of the hydride (dimHph)PH (13 ). X-ray structures of compounds3, 14, and (dimHph)PO2 CH (17 ) are also discussed.